Генетическое разнообразие культурных диплоидных видов пшеницы по ISSR-маркерам - Твердохлеб, Е.В.; Богуславский, Р.Л.; Акинина, Г.Е.; Попов, В.Н.; Анциферова, О.В.; Шелякина, Т.А.; Ильченко, Н.К. (Фактори експериментальної еволюції організмів, 2016)
Aim. The assessment of cultivated einkorn genetic diversity from the collection of the National Centre of Plant Genetic
Resources of Ukraine. Methods. Analysis of genetic diversity was performed using ІSSR markers. Results. 82 DNA loci
were identified. The high level of polymorphisms is found – in average 80%. Almost all the samples revealed the unique
fragments. Based on the ІSSR markers, 14 accessions were grouped into three clusters. The first cluster includes nakedgrain accession T. sinskajae and the sample with easy threshing UA0300113, the third cluster includes the accessions
with most difficult grain threshing. To increase the genetic diversity of T. monococcum, there is advisable to carry out
crossbreeding between the sample UA0300117 on the one hand and the samples UA0300113, UA0300221, UA0300222
on the other hand. Conclusions. The investigated set of accessions is rather high polymorphic. Clustering of cultivated
einkorn accessions using ISSR markers is not correlated with geographic origin.
Keywords: T. monococcum, Т. sinskajae, ІSSR markers, genetic diversity, genetic distances.